Assessment of Sacroiliitis at Diagnosis of Juvenile Spondyloarthritis by Radiography, Magnetic Resonance Imaging, and Clinical Examination. Issue 2 (February 2016) - Weiss, Pamela F.; Xiao, Rui; Biko, David M.; Chauvin, Nancy A.
Abstract : Objective: To evaluate the prevalence of sacroiliitis at diagnosis of juvenile spondyloarthritis (SpA) and the accuracy of physical examination and back pain to detect sacroiliitis, using imaging as the reference standard. Methods: We performed a prospective cross‐sectional study of 40 children with newly diagnosed juvenile SpA and 14 healthy controls. Subjects were assessed using physical examination, anteroposterior pelvic radiograph, and pelvic magnetic resonance imaging (MRI). Differences in clinical features between those children with and without sacroiliitis were assessed by Fisher's exact test for categorical variables and Wilcoxon's rank sum test for continuous variables. Accuracy of physical examination and back pain for detection of sacroiliitis was determined using MRI as the reference standard. Predicted probability of sacroiliitis was determined using exact multivariate logistic regression. Results: Eight children (20%) with juvenile SpA had active sacroiliitis. Of those subjects with active changes on MRI, 7 of 8 (88%) also had evidence of erosions or sclerosis. Five children (13%) with juvenile SpA and 1 control (7%) had nonperiarticular bone marrow edema. Of the subjects with active sacroiliitis, only 3 (38%) reported a history of back pain or tenderness on palpation of the sacroiliac joints. The positive and negative predictive values of clinical examination features and back pain for detection of sacroiliitis were low. The estimated probability of having sacroiliitis was 0.84 (95% confidence interval 0.40–1.00) in HLA–B27–positive patients with an elevated C‐reactive protein (CRP) level. Conclusion: Active sacroiliitis by MRI is common at diagnosis in juvenile SpA and is frequently asymptomatic. Children who are HLA–B27–positive and have elevated CRP levels have the highest probability of sacroiliitis.